2006
DOI: 10.1111/j.1440-1754.2006.00945.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal foreign body in childhood: A multidisciplinary approach

Abstract: A 5-year-old girl referred to our division for evaluation of persisting foul-smelling brown vaginal discharge with pruritus for over 2 years, not corresponding to antibiotic therapy. Transabdominal ultrasound identified a heterogeneous mass intensely fixed in the upper third of vaginal wall. Vaginography revealed a filling defect in the upper part of vagina, confirming the diagnosis of an intravaginal foreign body. The foreign body was grasped and removed by traction; it turned out to be a thin double-wrapped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…Vaginal foreign bodies in children require examination under anesthesia [7,9]. Removal demands both special expertise and instruments, along with a pediatric anesthetic service that is rarely available in low-income countries [14,22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Vaginal foreign bodies in children require examination under anesthesia [7,9]. Removal demands both special expertise and instruments, along with a pediatric anesthetic service that is rarely available in low-income countries [14,22].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a lack of adequate blood transfusion facilities and other services in rural settings can adversely affect outcome [22]. Currently, despite concerted developmental health sector efforts, most of the first referral units in the reproductive and child health program in rural India are not well equipped to provide adequate management, especially when the extent and severity of injuries requires examination under anesthesia with a multidisciplinary approach [9,12,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors have also reported a method performed by ultrasonography consisting of the use of three-dimensional saline infusion vaginography as an adjunctive modality in the same indications (13). Vaginography has also been described to allow the indirect visualization of an intravaginal foreign body in childhood (14). We can draw the following conclusions from this case: VF represents a condition with profound and devastating consequences for the patient.…”
Section: Answermentioning
confidence: 62%